Digital subtraction angiography in coronary artery bypass graft assessment: clinical applicability. Issue 4 (October 1985) - Hayward, R; Hunter, G J
Abstract : Application of electrocardiogram gated digital subtraction angiography to the assessment of coronary artery bypass graft function was studied one week to eight years after bypass operation in ten unselected patients with recurrent chest pain. For the digital method, contrast was injected into the ascending aorta via a 4 or 5 French gauge catheter. The results of this technique were compared with those of selective graft and coronary angiography in the same patients by two independent observers. Of twenty six grafts in the series, patency was confirmed in twenty one by both selective and digital angiography. The quality of graft run off, graded by each observer using a simple scoring system, demonstrated six points of inter observer disagreement when standard cineangiograms were used, compared with nine points of disagreement when digital images were used. Digital subtraction angiography provided useful graft visualisation, but was less good than conventional angiography at defining the native coronary circulation. The role of this promising new technique has yet to be established.